A Replenishment inventory model for items under time-varying demand rates considering trade credit period and cash discount for a finite time horizon - Mohd Omar, (Universiti Kebangsaan Malaysia, 2012)
Many researchers have developed various economic ordering quantity models by assuming an infinite time horizon and constant demand rate. However due to rapid technological advancement, shorter product life cycle and severe competition, those assumptions are no longer realistic. In this paper, we complement that shortcoming by considering an inventory model that satisfies a continuous time-varying demand rate for a finite time horizon when trade credit period and unit cash discount are allowed. The time horizon consists of n different cycles with equal or different cycles length. The trade credit period was assumed to be proportional to the cycle length. We developed mathematical models and presented a numerical example to support the effectiveness of these models.